Singing in Tune: Berimbau Tuning and Song Mode in Capoeira (1937–1978) - Juan Diego Díaz; Alex Rossi (Analytical Approaches to World Music, 2024)
The berimbau musical bow is the signature instrument of the Afro-Brazilian art of capoeira. Alone or in groups of two or three, it leads the capoeira’s ensemble by creating various kinds of grooves that accompany songs and physical games. As pitched instruments, they have the potential to guide singers melodically or even harmonically. In practice, however, practitioners rarely talk about precise bow tuning or singing tonalities and their approaches are widely diverse. This article investigates the tuning of the berimbau and the relationship between berimbau tuning and song mode. Our goal is to infer the most common tuning and singing practices used by practitioners through a systematic study of field recordings by foreign researchers, commercial albums by practitioners, movies, documentary films, TV programs, and transcriptions of capoeira music from the 1937 – 1978 period, a formative period in the development of modern capoeira. With a method combining musical analysis at tonal and microtonal level, we analyze a corpus of 448 songs to propose a five-tier taxonomy of relationships between tuning and mode: (1) Direct tonicization, when singers directly tonicize one of the berimbau pitches; (2) Indirect tonicization, when singers use one of the bow pitches as an indirect reference—the berimbau is not tuned to the song’s fundamental but to a different scale degree such as the third or the fifth; (3) Chordal tonicization, when berimbau pitches form a dyad or triad that sets up the singing mode; (4) Overtone tonicization, when singers tonicize not a bow note but one of its prominent overtones; and (5) Non-tonicization, when singers seem to disregard bow pitches. We propose that these categories of tonicization may correspond to unspoken ideal aesthetics that practitioners developed in the 1937 – 1978 period and persist today.